Políticas de classificação/classificações políticas: o exemplo das propriedades rácicas/características somáticas no BI - Reis, Fidel (Africana Studia, 2020)
According to the law approved by the National Assembly of Angola, the 26th of June 1996, 'race' is one ofthe identifying features present in the Identity Card. The reasons for the inclusion of such a controversial criterion constitute the starting point of my study. It was my purpose to reflect on the identity configurations based on classifications using racial properties and their role in the politica! arena of Angola. For this, I have combined a socio-historical theoretical framework with the results of the empirical research I did in Luanda.